Athletes and Skin Health: Managing Risks and Essential Care Strategies - Dewi, Arifiana Wungu Kartika; Solikah, Nur Luthfiatus; Kumalasari, Diah Ngesti (Journal of Unified Multidisciplinary Practice in Sports, Health, and Medicine, 2026)
Background: Exercise enhances cardiovascular and muscular health, as well as skin health, by boosting circulation, facilitating detoxification, and alleviating stress. Physical activity improves circulation, supplying nutrients and oxygen to the skin, so facilitating cellular regeneration, wound healing, and acne prevention. Moreover, exercise enhances collagen synthesis, thereby preserving skin suppleness, decelerating aging, and facilitating skin rejuvenation. Content: Exercise can markedly enhance physical health; however, it also presents several dangers to skin health, including UV exposure, skin irritation, dehydration, and allergies. Extended sun exposure elevates the risk of skin cancer and photoaging, but friction from constrictive garments and perspiration may result in irritation and conditions such as folliculitis. Dehydration and allergic reactions, induced by ambient elements or compounds in athletic equipment, intensify skin problems, rendering effective preventive measures such as sunscreen application, hydration, and appropriate attire crucial for athletes. Conclusion: Consistent physical exercise has substantial advantages for general physical and mental well-being; nevertheless, it may also present concerns to skin health, particularly for athletes training outside. Prevalent concerns encompass UV-induced damage, friction-related irritation, dehydration, and allergic reactions stemming from contact with diverse materials and skincare products. Athletes are recommended to employ high-SPF sunscreen, don UV-protective apparel, maintain hydration, and adhere to a post-exercise skincare regimen to replenish moisture and restore barrier function.